Sex pheromone components of Diatraea considerata (Heinrich) (Lep., Pyralidae) - Gries, Regine (1998)
Three aldehydes. (Z)-11-hexadecenal (Z11–16:Ald), (Z)-7-hexadecenal (Z7–16:Ald) and (Z)-13-octadecenal (Z13–18:Ald), in a ratio of 74:23:3 are female-produced sex pheromone components of the pyralid moth, Diatraea considerata (Heinrich). Compounds extracted from pheromone glands were identified by coupled gas chromatographic-electroantennographic detection (GC-EAD) and coupled GC-mass spectrometry (MS). In field trapping experiments, Z11–16:Ald, Z7–16:Ald or Z13–18:Ald singly were behaviourally inactive, but in ternary combination were as attractive as virgin females. Deleting either Z11–16:Ald or Z7–16:Ald from the ternary aldehyde blend strongly reduced attractiveness indicating that these two compounds are most important for attraction of males. Congeneric and sympatric female D. grandiosella (Dyar) also utilize Z11–16:Ald and Z13–18:Ald as sex pheromone components. Production of Z9–16:Ald by female D. grandiosella and Z7–16:Ald by female D. considerata contributes to the specificity of pheromone blends but does not prevent cross-attraction of heterospecific males. In sugarcane plantations, aldehyde (Z11–16:Ald, Z7–16:Ald and Z13–18:Ald)-impregnated lures may replace females as trap baits to monitor population densities of D. considerata.